Pengembangan Nata de Coco ala UD Citra Rasa - Muhamad Fitrah Arjuna; Dedi Junaedi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
Micro, small and medium enterprises or MSMEs refer to the types of small businesses that have a net worth of at most Rp. 200 million, excluding land and buildings where the business is located. MSMEs have proven to be resilient and able to withstand the economic crisis and monetary crisis in Indonesia. This paper aims to analyze UD Nata de Coco Citarasa in Bogor. The method used is descriptive qualitative analysis with a case study approach, observation and interviews. The result is . which is named the image of the taste of nata de coco, with the results of my interview with the owner that UD Nata de Coco is managed with a very simple management. Starting from the production process to marketing, and the production process is still using manually, there are no modern machines. Only use the tools in the kitchen in the production process. Marketing of their products is still not widespread, only by selling to small shophouses, and using word of mouth information, not using a separate website such as online sales. As a home-based business, financial management is still modest, not yet systematically following accounting standards. The financial reports are still integrated with the family finances.